Altered brain function underlying verbal memory encoding and retrieval in psychotic major depression - Kelley, Ryan (2012)
Psychotic major depression (PMD) is associated with deficits in verbal memory as well as other cognitive impairments. This study investigated brain function in individuals with PMD during a verbal declarative memory task. Participants included 16 subjects with PMD, 15 subjects with non-psychotic major depression (NPMD) and 16 healthy controls (HC). Functional magnetic resonance imaging (fMRI) data were acquired while subjects performed verbal memory encoding and retrieval tasks. During the explicit encoding task, subjects semantically categorized words as either “man-made” or “not manmade.” For the retrieval task, subjects identified whether words had been presented during the encoding task. Functional MRI data were processed using SPM5 and a group by condition ANOVA. Clusters of activation showing either a significant main effect of group or an interaction of group by condition were further examined using t-tests to identify group differences. During the encoding task, the PMD group showed lower hippocampus, insula, and prefrontal activation compared to HC. During the retrieval task, the PMD group showed lower recognition accuracy and higher prefrontal and parietal cortex activation compared to both HC and NPMD groups. Verbal retrieval deficits in PMD may be associated with deficient hippocampus function during encoding. Increased brain activation during retrieval may reflect an attempt to compensate for encoding deficits.